Predicting Indonesian Consumers’ Intention to Buy Green Cosmetics Using The Modified TPB Framework - Nicholas Wilson; Edelyn Edelyn (Universitas Bunda Mulia, 2022)
This study was conducted in order to determine some reasons or factors which could motivate or influence consumers’ intention to purchase or buy green cosmetics which were marketed in Indonesia. Using and adopting the modified version of the theory of planned behavior (TPB) framework, this study attempted to assess the role of three factors, namely attitude, perceived price and subjective norms, in affecting and influencing Indonesian consumers’ purchase intention to buy green cosmetics. Using and implementing survey method, questionnaires were chosen as the main tools for collecting and gathering all of the data needed from the respondents, in which, all of these questionnaires were distributed to all respondents in a virtual manner using google forms. Respondents who participate in this study are consumers who’ve purchased or bought any kinds of green cosmetic products from any brands which were sold in Indonesia at least twice (2x) for the past 1 year. A non-probability sampling method in the form of purposive sampling method was implemented in order to ensure the conformity of the respondents with the respondents’ criteria set in this study. A total of 786 data were collected all of the respondents, in which, after conducting thorough analysis and assessment concerning the all of these data, a total of 54 data were omitted due to incomplete or unsuitable responses, thus confirming that 732 data were usable to be assessed in this study. Using PLS-SEM method, authors concludes that all three variables, which are attitude, perceived price, and subjective norms play significant roles in affecting consumers’ intention toward buying green cosmetics in Indonesia